2017
DOI: 10.1111/mcn.12471
|View full text |Cite
|
Sign up to set email alerts
|

Timing of solid food introduction and association with later childhood overweight and obesity: The IDEFICS study

Abstract: This study investigated associations between timing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 42 publications
6
60
2
10
Order By: Relevance
“…Our marginal association between late age at SF introduction and obesity at age 5 is in accord with other studies . Specifically, in a small sample ( n = 54) of children enrolled in a prospective cohort study within 1 week of birth, delaying SF introduction to later than 5 months was related to higher BMI at 3 and 6 years of age .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our marginal association between late age at SF introduction and obesity at age 5 is in accord with other studies . Specifically, in a small sample ( n = 54) of children enrolled in a prospective cohort study within 1 week of birth, delaying SF introduction to later than 5 months was related to higher BMI at 3 and 6 years of age .…”
Section: Discussionsupporting
confidence: 91%
“…In a cross‐sectional, population‐based study (2007 to 2011), both early (4 months) and late (≥ 7 months) introduction of SF increased the odds of BMI > 97.7th percentile at ages 9 to 15 months with ORs of 1.75 and of 2.64, respectively . Papoutsou et al also demonstrated a 38% higher odds of childhood overweight/obesity (ages 2 to 9 years) among exclusively breastfed infants with introduction of SF at ≥ 7 months of age using cross‐sectional data from eight European countries (2007 to 2008) .…”
Section: Discussionmentioning
confidence: 99%
“…Cross-sectional data from eight European countries found almost 40 % lower odds of childhood overweight/obesity (ages 2-9 years) in children who were introduced to solids right after 6 months of EBF and continued to receive breast milk (≥12 months) (39) . A large population-based study from Australia with 3153 children found that early solid-food introduction (before 4 months) was associated with increased odds of above normal BMI at 1 year of age, regardless of child BF status at 4 months of age (40) .…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the observational evidence related to breastfeeding, no clear association between the age of introduction of solid food and childhood obesity has been found [ 14 , 18 , 19 , 20 , 21 ]. Several studies have reported an interaction between the age of introduction of solid food and duration of breastfeeding, with the early introduction of solid food (i.e., <4 months) being associated with increased weight gain only for infants breastfed for less than four to five months [ 22 , 23 , 24 ], but not in infants that were breastfed for longer.…”
Section: Introductionmentioning
confidence: 99%